Production of Xylose from Oil Palm Trunk - Siti Nafsiah, Mohamed Omar (2013)
Oil palm trunk is an oil palm biomass which is the renewable source for the production of many useful products, such as xylose. The study provides efficient analysis on optimizing xylose concentration, in order to obtain higher productivity and yield of xylitol. Xylose is safe, healthy, toxin free substance that can allow people to enjoy the flavor of sugar without negative effects on the body. The objectives of this study are to produce valuable products (xylose and xylitol) from waste oil palm trunk, to identify the effects of sulfuric acid concentration and hydrolysis time on the production of xylose from oil palm trunk. The hydrolysis of oil palm trunk powder was carried out by contacting powder with 3%, 5% and 7% sulfuric acid at 60 °C for 60, 120 and 180 minutes. The acid hydrolysis is using sulfuric acid wood mass ratio of 8: 1 g/g. After hydrolysis reaction, solid part was removed by filtration and the filtrate was neutralized with CaCO3 and then undergoes detoxification process by using activated carbon powdered with the mass ratio 10:1 of hydrolysate/charcoal powder. The percentage of xylose will be analyzed from the hydrolysate by using High Performance Liquid Chromatography machine. From the literature, the results obtained was the higher acid concentrations led to higher sugar recovery but longer hydrolysis’s time caused lower amount in sugar recovery. For a conclusion, the high value products which are xylose can be produce from waste oil palm biomass.